Singularity of Novel Discourse in Dostoevsky’s The Idiot - Horváth, Géza (Slavica, 2023)
The article examines Dostoevsky’s novel discourse as a singular unity in the novel The Idiot. This discourse is dominated by the principle of indeterminacy, and the category of subjectivity is closely connected with the novel model of singularity. The aim of the article is to understand the principles of discursive unity organization in the novel on the level of its basic metaphors. These basic metaphors are "point" and "line".